Association between market concentration of hospitals and patient health gain following hip replacement surgery - Feng,Y; Pistollato,M; Charlesworth,A; Devlin,N; Propper,C; Sussex,J (Journal of Health Services Research and Policy, 2015)
ObjectivesTo assess the association between market concentration of hospitals (as a proxy for competition) and patient-reported health gains after elective primary hip replacement surgery.MethodsPatient Reported Outcome Measures data linked to NHS Hospital Episode Statistics in England in 2011/12 were used to analyse the association between market concentration of hospitals measured by the Herfindahl-Hirschman Index (HHI) and health gains for 337 hospitals.ResultsThe association between market concentration and patient gain in health status measured by the change in Oxford Hip Score (OHS) after primary hip replacement surgery was not statistically significant at the 5% level both for the average patient and for those with more than average severity of hip disease (OHS worse than average). For 12,583 (49.1%) patients with an OHS before hip replacement surgery better than the mean, a one standard deviation increase in the HHI, equivalent to a reduction of about one hospital in the local market, was associated with a 0.104 decrease in patients’ self-reported improvement in OHS after surgery, but this was not statistically significant at the 5% level.ConclusionsHospital market concentration (as a proxy for competition) appears to have no significant influence (at the 5% level) on the outcome of elective primary hip replacement. The generalizability of this finding needs to be investigated.